Prevalence and predictors of anxiety disorder courses in the Canadian Armed Forces. (December 2022) - Pankratz, Lily; Sommer, Jordana L.; Bolton, Shay-Lee; Sareen, Jitender; Enns, Murray W.; Afifi, Tracie O.; El-Gabalawy, Renée; Mota, Natalie
Abstract: Few studies have examined the longitudinal courses of anxiety disorders in military members. This study examined the prevalence and predictors of courses of any anxiety disorder in members and veterans of the Canadian Armed Forces, including no lifetime, remitted, new onset, and persistent/recurrent anxiety disorder. The 2018 Canadian Armed Forces Members and Veterans Mental Health Follow-up Survey is a 16-year follow-up of n = 2941 participants from the Canadian Community Health Survey: Canadian Forces Supplement in 2002. Diagnoses of any DSM-IV anxiety disorder (i.e., generalized anxiety, social anxiety, and/or panic disorder) in 2002 and 2018 were used to create four anxiety course groups. A large proportion of the sample (36.3 %; new onset = 24.6 %, remitting = 6.9 %, and persistent/recurrent = 4.8 %) met criteria for an anxiety disorder during one or both time points. Factors at baseline and/or between 2002 and 2018, including income, education, military rank, comorbidity of PTSD or depression, deployment history, and traumatic events, were positively associated with most anxiety courses relative to no anxiety in analyses. Targeted interventions are needed to help mitigate anxiety disorders among this population. Social support and active coping were protective factors for most anxiety courses and may need to be incorporated into targeted interventions. Highlights: A large proportion of military personnel met criteria for an anxiety disorder in 2002 and/or in 2018. Social support and active coping are protective factors for all anxiety courses. Lower income, education, and military rank were positively associated with all anxiety courses.